Posisi Kebijakan Dividen Sebagai Mediator Dalam Relasi Antara Profitabilitas, Likuiditas Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Anissa Dewi Safitri; Ana Kadarningsih (LPPM Politeknik Pratama, 2025)
This study aims to evaluate the role of dividend policy as a mediator in the relationship between profitability, liquidity and the assessment of the impact of firm growth on firm value in the real estate and property industry listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The results of the quantitative method using WarpPLS 8.0 analysis show that firm value is strongly influenced by profitability and firm growth, both directly and indirectly through dividend policy, which acts as a partial mediator. In contrast, liquidity has no significant impact on dividend policy or firm value. These findings confirm the importance of dividend policy as a strategic tool to improve market perception and firm value, while providing insights for more effective financial management in the real estate sector.